2020
DOI: 10.1113/jp280578
|View full text |Cite
|
Sign up to set email alerts
|

IRBIT activates NBCe1‐B by releasing the auto‐inhibition module from the transmembrane domain

Abstract: Key points The electrogenic Na+/HCO3−cotransporter NBCe1‐B is widely expressed in many tissues, including pancreas, submandibular gland, brain, heart, etc. NBCe1‐B has very low activity under basal condition due to auto‐inhibition, but can be fully activated by protein interaction with the IP3R‐binding protein released with inositol 1,4,5‐trisphosphate (IRBIT). The structural components of the auto‐inhibition domain and the IRBIT‐binding domain of NBCe1‐B are finely characterized based on systematic mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 79 publications
1
20
0
Order By: Relevance
“…of NBCe1-B under a given [Na + ]. Note that, the single molecular activity of NBCe1-A is several-fold greater than that of NBCe1-B (McAlear et al 2006;Su et al 2021). Again, the data are consistent with our conclusion that the substrate affinity is an intrinsic property of NBCe1.…”
Section: No Cooperativity For Substrate Binding In Nbce1supporting
confidence: 90%
See 3 more Smart Citations
“…of NBCe1-B under a given [Na + ]. Note that, the single molecular activity of NBCe1-A is several-fold greater than that of NBCe1-B (McAlear et al 2006;Su et al 2021). Again, the data are consistent with our conclusion that the substrate affinity is an intrinsic property of NBCe1.…”
Section: No Cooperativity For Substrate Binding In Nbce1supporting
confidence: 90%
“…In a previous study, if an oocyte expressing NBCe1-A was continuously perfused in CO 2 /HCO 3 − solution and two electrophysiology recordings were sequentially acquired at the beginning of and 4 min after the perfusion in CO 2 /HCO 3 − , a large shift towards positive in the V rev was observed for the second I NBC , eliciting a great inward current at −160 mV (Fig. 1D; Su et al 2021). This last observation provides a clear evidence for the effect of intracellular [Na + ] and [HCO 3 − ] on V rev .…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…It was found that in the hydrophilic N-terminus of the Na + /HCO 3 − co-transporter, the presence of charged (positively as well as negatively) residues is essential to fulfilling the autoinhibitory function of the transporter (Su et al, 2021). To corroborate the role of the N-terminus in the regulation of Hs NHA2 activity, we compared the sequences of unique homologs of NHA2 from various metazoan species (Fig.…”
Section: Resultsmentioning
confidence: 99%